O26 In situ simulation and improving patient care. (November 2018) - Robinson, David; Clegg, Eleanor; Harrison, Tracey; Credland, Tim; Jackson, Angela
Abstract : Background: We identified a problem with the communication of lessons learnt from complaints and Serious Incidents (SIs). We introduced monthly simulated scenarios to the team working in the Emergency Department (ED) from November 2016 to be the conduit for this information deliverance. This was part of a wider action plan to improve the care of the deteriorating patient. Summary of work: The scenarios last approximately 30 min followed by a debrief. We use the session to explore hospital and departmental systems as well as discussing the technical skills and human factors demonstrated. Following this we welcome feedback from the staff involved. We recognised the importance of sharing the lessons learnt from the simulation as well as the original case with all staff. This is achieved by the completion of the 'A+E Sim News' that is placed in poster format around the department as well as disseminated electronically. We have found that staff members read the one page A4 newsletter, particularly if placed on the back of the toilet door! Summary of results: Multi-professional in situ simulation has played a pivotal role in the improvement of care in the ED. We have demonstrated a 17% reduction in total ICU admissions since the introduction of the simulation programme, and a reduction in SIs related to the deteriorating patient (6 in 2016, 0 in 2017). Discussion and conclusions: As well as being a powerful educational tool the simulations have helped us identify latent risks, including knowledge of departmental policies and location of essential equipment and medications. The teaching sessions are becoming part of a cultural change to valuing quality education and sharing lessons learnt with the whole department. Anecdotally staff are asking when the next session is, suggesting scenarios and sharing learning by word of mouth. The programme was introduced as one facet of a quality improvement project which aimed to improve the care of the deteriorating patient. Outcomes from this project include a reduction in Serious Incidents (SIs) related to the deteriorating patient, and a reduction in ICU referrals. Recommendations: We recommend that practitioners and educators consider using in situ simulation as a tool to drive quality improvement. We have identified that sessions can be cancelled or shortened due to clinical demands. Taking the project forward, we intend to implement a rota for delivering the monthly sessions to promote sustainability of the project, with involvement of the whole consultant body.